Cliff diving: water impact and video-analysis - Napolitano, S. (Journal of Physical Education and Sport, 2014)
The sport of cliff diving was born fifteen years ago, and has gained enormous success. Barcellona in 2013, in light of the World Swimming Championships, the International Swimming Federation (FINA) has added this sport among the official swimming disciplines present in the competition. This highly spectacular sport complies particular motary and psychological abilities, which are not possible to train for lack of specific sports facilities. In competitions, the starting platforms are at a height of 25-28 meters, and the impact with the water is at a high velocity that stimulates the entire body in little time . The goal is to calculate the impact with the water, its form and the hypothetical consequences on the body using video training Methods. This study uses three distinct approaches: a case study of single performances, the descriptive research for the contribution of the evaluation of the analyst, and the constitution and elaboration of the data for the contribution of the physics expert. The model consists in the total of three performances of three international competitions: •2 Red Bull Cliff Diving World Series competitions •1 World Championship competition The single dives were analyzed, compared with overlapping displays of the performances, the analysis and decoding of the video given by the analyst and the technical expert in the field on water entry with Kinovea software. This specific software was used for simulations…data of coefficient of water impact and entry. Results. For each dive impact incidence and eventual consequences on the athlete were calculated. For each athlete both the positive and the negative aspects of their performances were located. The evaluation of the data collected (each single dive for each single athlete, total nine dives each) allowed an individual hypothetical model to use pre-competition. Conclusions. The results can be used by the athletes themselves, using the video education method, and by technical trainers for training, for the analysis and specific evaluation during competitions. Furthermore, a more in depth study will be able to demonstrate the danger and the consequences on the athletic organism in Olympic competition.